2022
DOI: 10.54600/igdirsosbilder.980917
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting The Perceived Stress Levels of University Students During The Coronavirus (COVID-19) Outbreak

Abstract: Bu çalışma Koronavirüs pandemi sürecinin üniversite öğrencilerinde algılanan stres seviyelerini etkileyen etmenlerin belirlenmesi amacıyla yapılmıştır. Materyal ve Metod: Çalışma, Ocak 2021 ile Şubat 2021 tarihleri arasında Türkiye'nin Doğu Anadolu Bölgesinde bulunan bir üniversitesinin öğrencileri ile yürütülmüştür.Çalışma 728 öğrenci ile tamamlanmıştır. Çalışmanın anket formları "Google Formlar" ile düzenlenerek bireylere gönderilen bağlantı linki ile toplanmıştır. Veri toplamada "Kişisel Bilgi FormunaAit So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…There are a large number of studies reporting that perceived stress differs in terms of gender (Demir, 2019;Eraslan,2016;Güney et al,2021b;Keleş et al,2022;Özgan et al, 2008;Savcı and Aysan,2014). On the other hand, there are also studies reporting that perceived stress does not differ in terms of gender (Bilgel et al,2007;Hevedanlı and Çakmak,2005;Şanlı, 2017;Uzun et al,2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a large number of studies reporting that perceived stress differs in terms of gender (Demir, 2019;Eraslan,2016;Güney et al,2021b;Keleş et al,2022;Özgan et al, 2008;Savcı and Aysan,2014). On the other hand, there are also studies reporting that perceived stress does not differ in terms of gender (Bilgel et al,2007;Hevedanlı and Çakmak,2005;Şanlı, 2017;Uzun et al,2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the level of positive thinking will be high in parallel with the high psychological well-being. In their study, Keleş et al (2022) found that during the COVID-19 process, university students had higher than moderate level of perceived stress and lower than moderate level of perceived coping. Due to the problems university students have in their daily lives, they experience common mental disorders such as stress and depression and this has become a global anxiety for university students (Keleş et al,2022;Othman et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation